A New Approach to Sensor Energy Saving Algorithm - Peng Zhu; Fei Jia (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Wireless sensor network energy saving algorithm is a popular topic in recent researches. This paper proposes a new LEACH based energy saving algorithm to prolong the life of wireless sensor network. In this algorithm, sensors are divided into several static clustering. And each sensor takes turns to act as clustering head. Meanwhile, in order to reduce the network communication flow, the algorithm transports as little control signals as possible. Simulation results show that the algorithm proposed by this article is better than traditional fixed energy saving clustering algorithm in prolonging network’s life cycle. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2478